Sirtuins and redox signaling interplay in neurogenesis, neurodegenerative diseases, and neural cell reprogramming - Mormone, Elisabetta; Iorio, Eugenio Luigi; Abate, Lucrezia; Rodolfo, Carlo (Frontiers in Neuroscience, 2023)
Since the discovery of Neural Stem Cells (NSCs) there are still mechanism to be clarified, such as the role of mitochondrial metabolism in the regulation of endogenous adult neurogenesis and its implication in neurodegeneration. Although stem cells require glycolysis to maintain their stemness, they can perform oxidative phosphorylation and it is becoming more and more evident that mitochondria are central players, not only for ATP production but also for neuronal differentiation’s steps regulation, through their ability to handle cellular redox state, intracellular signaling, epigenetic state of the cell, as well as the gut microbiota-brain axis, upon dietary influences. In this scenario, the 8-oxoguanine DNA glycosylase (OGG1) repair system would link mitochondrial DNA integrity to the modulation of neural differentiation. On the other side, there is an increasing interest in NSCs generation, from induced pluripotent stem cells, as a clinical model for neurodegenerative diseases (NDs), although this methodology still presents several drawbacks, mainly related to the reprogramming process. Indeed, high levels of reactive oxygen species (ROS), associated with telomere shortening, genomic instability, and defective mitochondrial dynamics, lead to pluripotency limitation and reprogramming efficiency’s reduction. Moreover, while a physiological or moderate ROS increase serves as a signaling mechanism, to activate differentiation and suppress self-renewal, excessive oxidative stress is a common feature of NDs and aging. This ROS-dependent regulatory effect might be modulated by newly identified ROS suppressors, including the NAD+-dependent deacetylase enzymes family called Sirtuins (SIRTs). Recently, the importance of subcellular localization of NAD synthesis has been coupled to different roles for NAD in chromatin stability, DNA repair, circadian rhythms, and longevity. SIRTs have been described as involved in the control of both telomere’s chromatin state and expression of nuclear gene involved in the regulation of mitochondrial gene expression, as well as in several NDs and aging. SIRTs are ubiquitously expressed in the mammalian brain, where they play important roles. In this review we summarize the current knowledge on how SIRTs-dependent modulation of mitochondrial metabolism could impact on neurogenesis and neurodegeneration, focusing mainly on ROS function and their role in SIRTs-mediated cell reprogramming and telomere protection.